ANALISIS JARAK LEMPARAN FLYROCK AKIBAT KEGIATAN PELEDAKAN DI CV KALIMANTAN MAKMUR KOTA PALANGKA RAYA - Ningsih, Sonia Ayu; Wijaya, Doddy Ariyantho Kusma; Indrajaya, Fahrul (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2024)
The mining method used by CV Kalimantan Makmur is blasting. One of the impacts of blasting is flying rocks (flyrock). At the quarry and crusher locations at CV Kalimantan Makmur, they are close together, and sometimes geometric mismatches or excessive explosives cause excessive flyrock throwing and the direction of the flyrock is not in accordance with estimates. For this reason, a prediction model for the throw distance is needed that is close to the actual distance to optimize the geometry to increase safety from the impact of blasting. The research method uses a quantitative descriptive method. Data collection uses direct measurement methods, tracker software, and theories. The study obtained the results of 8 actual field observations of the flyrock distance, one of which reached 311 meters, and other observations at a distance of 40-60 meters. From the evaluation results, it was due to excessive explosive filling in one of the holes. While based on the flyrock tracker software, the furthest is 63.03 meters, and the other is 40-70 meters, the percentage difference is -9.98%, almost close to the actual. Predictions according to Richard & Moore obtained 140.37 meters of face busting, 92.63 meters of cratering, and 64.2 meters of rifling. The percentage is close to the actual face bursting, it is recommended to pay attention to the burden distance to reduce the distance of the flyrock throw. While the prediction of parabolic motion, the furthest distance is 92.63 meters, approaching a quarter of the actual flyrock distance. The conclusion from the results obtained, it is recommended to control the flyrock stemming length or the material used.